Lubrication oil system design for a new 4-strokes single-cylinder engine cylinder head - Muhammad Afiq, Zali (2009)
Reliability and performance of modern engines are directly dependent on the effectiveness of lubricating systems. To be effective, an engine lubricating system must successfully perform the functions of minimizing friction between the bearing surfaces of moving parts, dissipating heat, and keeping the engine parts clean by removing carbon and other foreign matter. In almost all modern internal-combustion engines, the system that provides the lube for these functions is the forced-lubrication system. Although there are many variations in lubricating systems for internal-combustion engines, the components and method of operation are basically the same. Steady state thermal analysis is carried out for the thermal fluid flow in the engine. Solidwork software is used for modeling the design and steady state analysis. The upper piston with variation of groove has been design for this simulation. For each piston, four different radius of groove design at the upper piston are use to analyze the thermal effect to the cylinder head and engine oil temperature. For conclusion, the quality of engine lubrication depends upon how much oil is supplied and how the lubricant is fed under thermal load of the components. This state of lubrication is closely related to the safe operation of an engine and its lifetime. Therefore, a practically optimized analytical method has been required by engine designers.